Kebijakan Penguatan Tanggung Jawab Hukum Pemilik Hewan Penular Rabies dalam Menjamin Perlindungan Masyarakat di Provinsi Bali - Made Adi Widnyana (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2025)
Rabies remains one of the most significant zoonotic diseases threatening public health in Bali Province, Indonesia. The close interaction between local communities and rabies-transmitting animals, particularly dogs, combined with the low level of legal compliance among pet owners, continues to contribute to animal bite incidents and rabies transmission. This study aims to examine the legal responsibility of rabies-transmitting animal owners within the Indonesian legal system, evaluate the implementation of Bali Provincial Regulation Number 15 of 2009 concerning Rabies Control, and formulate a strengthened legal responsibility model capable of providing more effective public protection. This research employs normative legal research using statutory, conceptual, and case approaches. Primary legal materials consist of national and regional legislation governing animal health and rabies control, while secondary legal materials include scientific journals, legal textbooks, and previous research. The collected materials were analyzed qualitatively through legal interpretation and prescriptive legal analysis. The findings reveal that although legal obligations of pet owners have been regulated in various national and regional legal instruments, their implementation remains ineffective due to weak law enforcement, limited public legal awareness, and the predominance of informal family-based dispute resolution following animal bite incidents. This study proposes a collaborative legal responsibility model integrating local government, customary villages, veterinary authorities, and community participation through administrative sanctions, civil liability, criminal responsibility, and customary law enforcement. Such an integrated approach is expected to strengthen public legal protection while supporting the long-term realization of a rabies-free Bali.